LOSS OF COOLANT ACCIDENT ANALYSIS OF APR1400 REACTOR - LE , DAI DIEN; HOANG , MINH GIANG; LE , VAN HONG; LE , THI THU; VO , THI HUONG; NGUYEN , THI THANH THUY; NGUYEN , THI TU OANH; PHAM , TUAN NAM (Nuclear Science and Technology, 2011)
Several features of NPP with APR1400 nuclear reactor during a loss of coolant accidents (LOCAs) are investigated in this study. The paper describes some main design characteristics of the engineering safety features of APR1400 and the thermal hydraulic calculation results for steady-state using MARS and RELAP/SCDAPSIM codes. Two LOCA categories are simulated with maximum break sizes for each. The Large Break LOCA accident has been analyzed for the case of double end guilotine break and safety parameters are evaluated based on acceptable criteria for ECCS given by US NRC. The results from cold leg break LOCA with the broken area of 0,0465m2 are derived in comparison with reference case [4]. The scenarios for the LOCA are performed for high pressure injection system (HPIS) failed to operate, 2 and 4 HPIS pumps are activated respectively. The presented results in the paper are taken from the research project between INST’s researchers and KAERI experts in using RELAP5 tool for safety analysis of NPPs under supported by Ministry of Science and Technology (MOST).